Un modèle intersectoriel incluant une fonction d’investissement et des coefficients techniques variables - Beaudry, Richard; Nepveu, Jacques (L'Actualité économique, 1978)
Input-output analysis was always criticized for its inability to simulate all the effects produced by economic development; induced investment and its impact was notably one of the most serious lack usually noted. The model presented here is an attempt to prove that such a problem might well be solved in the future by introducing an investment function in the analysis at reasonable costs. By the same token, it tries to sell the possibility of taking into account the technological changes that occur in various industrial sectors, in allowing technical coefficients to change accordingly. The authors first briefly describe the economic rationale supporting the necessity of introducing such modifications in the static input-output analysis. Then, using the 1966 Quebec Input-Output table as the basic structure of their model, they formulate what could be presented as a fully dynamic (auto-regressive) model that can simulate the main effects that should be evaluated in an impact study: direct and indirect effects, and effects related to induced consumption and investment. Finally, running the model from a fictious variation in final demand and for a ten-year period, they conclude with the following results: 1°) the introduction of the accelerator increases by about 30% (the figure varies from 65% to 15% during the period) the impact that would have been otherwise obtained with the static model; and 2°) the use of actual technical coefficients (the introduction of technological changes) reduces by 20% the impact that would have been estimated without the modification.